The future of energy - Towler, Brian F. (Academic Press, 2014)
Using the principle that extracting energy from the environment always involves some type of impact on the environment, The Future of Energy discusses the sources, technologies, and tradeoffs involved in meeting the world's energy needs. A historical, scientific, and technical background set the stage for discussions on a wide range of energy sources, including conventional fossil fuels like oil, gas, and coal, as well as emerging renewable sources like solar, wind, geothermal, and biofuels. Readers will learn that there are no truly "green" energy sources-all energy usage involves some tradeoffs--and will understand these tradeoffs and other issues involved in using each energy source. Each potential energy source includes discussions of tradeoffs in economics, environmental, and policy implications. Examples and cases of implementing each technology are included throughout the book. Technical discussions are supported with equations, graphs, and tables. Includes discussions of carbon capture and sequestration as emerging technologies to manage carbon dioxide emissions.